2014
DOI: 10.1042/cs20130436
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) and angiotensin-(1–9): function in cardiac and vascular remodelling

Abstract: The RAS (renin-angiotensin system) is integral to cardiovascular physiology; however, dysregulation of this system largely contributes to the pathophysiology of CVD (cardiovascular disease). It is well established that AngII (angiotensin II), the main effector of the RAS, engages the AT1R (angiotensin type 1 receptor) and promotes cell growth, proliferation, migration and oxidative stress, all processes which contribute to remodelling of the heart and vasculature, ultimately leading to the development and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(151 citation statements)
references
References 113 publications
(175 reference statements)
3
146
0
2
Order By: Relevance
“…Indeed, previous studies have identified ACE2 as a negative regulator of the RAS by converting Ang II into Ang-(1-7), which, by acting via its own receptor Mas, can inhibit platelet adhesion and thrombosis formation, suppress inflammation, stabilize atherosclerotic plaques, promote myocardial remodeling and lower blood pressure. 8,[14][15][16] More recently, Ohshima et al found that elevated Ang-(1-7) expression could in turn upregulate the mRNA levels of ACE2 and ATR2 in the injured artery. 17 Their results suggested novel interactions between ACE2-Ang-(1-7)-Mas axis and ACE-Ang II-ATR2 axis in vascular remodeling and further revealed the multiple functions of ACE2 in protecting against the development and progression of vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies have identified ACE2 as a negative regulator of the RAS by converting Ang II into Ang-(1-7), which, by acting via its own receptor Mas, can inhibit platelet adhesion and thrombosis formation, suppress inflammation, stabilize atherosclerotic plaques, promote myocardial remodeling and lower blood pressure. 8,[14][15][16] More recently, Ohshima et al found that elevated Ang-(1-7) expression could in turn upregulate the mRNA levels of ACE2 and ATR2 in the injured artery. 17 Their results suggested novel interactions between ACE2-Ang-(1-7)-Mas axis and ACE-Ang II-ATR2 axis in vascular remodeling and further revealed the multiple functions of ACE2 in protecting against the development and progression of vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,7 Recently, a homolog of ACE, namely ACE2, has emerged as an important player in the pathophysiology of vascular diseases due to its protective role in metabolizing pro-inflammatory, pro-proliferative and pro-hypertensive Ang I and Ang II into favorable Ang-(1-9) and Ang-(1-7), respectively. 7,8 Despite a growing body of evidence on the importance of ACE family in the pathogenesis of arterial diseases, their involvement and functional roles in the setting of aortic aneurysmal dilatation and dissection are still unclear. Therefore, the present study was designed to assess the plasma ACE levels and the mRNA expression of ACE and ACE2 in aortic samples obtained from surgical patients with TAD and TAA, and to determine whether these proteinases contribute to the progression of aortic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…3.3 Angiotensin-converting enzyme 2 ACE2 is a carboxypeptidase known to cleave the C-terminal residues of AngI and AngII to Ang-(1--9) and Ang-(1--7), respectively [83,84]. By reducing levels of AngII and increasing levels of Ang-(1--7) and Ang-(1--9), ACE2 is believed to play a vital role in countering the effects of AngII on the cardiovascular system by activating AngII Type 2 receptor (AT2R) and the MAS receptor [85].…”
Section: B Raymer and D Ebnermentioning
confidence: 99%
“…An endogenous counter-regulatory axis of the RAAS exists centered on an ACE homologue ACE2 and generation of the active peptide hormone Ang-(1–7), which acts at the receptor Mas and can antagonize pathophysiological effects of Ang II at the AT 1 R (reviewed in McKinney et al [46]). Using in vitro cell culture models the first studies into the counter-regulatory axis of the RAAS have been performed to identify novel signaling mechanisms of the peptide hormone Ang-(1–7) [47].…”
Section: Experimental Models Of Hypertensionmentioning
confidence: 99%